The Hypotyposis of the monastery of the Theotokos Evergetis, Constantinople (11th-12th centuries) : introduction, translation and commentary /: introduction, translation and commentary. (2016) - Jordan, R. H; (Historian), Morris, Rosemary
No abstract available